La identidad cultural en los niños y niñas de las escuelas rurales. - Tigse Galarza, Tania Paulina (2018)
A nation is marked by the cultural identity, being an essential part of their culture, the traditions and customs set the context where the student develops his own image, and reflect upon as the transporter of rating culture abroad and show it to others with a sense of pride. The loss of cultural identity is one of the main problems that affect the students’ teaching-learning process who are in rural school, due to many factors; limited methodology according to the requirements of the rural context by teachers, among other factors which entails those students are afraid to identify with their culture. This research aims at identifying the factors that promote the loss of children’s cultural identity in rural schools to promote respect for customs and traditions at the "Coronel Germánico Rivadeneira" School of Basic Education. The research topic has a quantitative approach, which is expressed in the use of an instrument that allows at collecting numerical or statistical data of a population to determine the phenomenon of the research problem together with its causes and effects. This research is important because the educational community must be interested in working as a team to rescue traditions immersed in the local culture, thus solving social, academic problems and others, the work will be a great impact because this will be worked with students, teachers and parents to contribute to the students ‘development and training, achieving a focus reflected in the continued acceptance of cultural identity.